2017
DOI: 10.1097/psy.0000000000000364
|View full text |Cite
|
Sign up to set email alerts
|

Positive Self-Perceptions of Aging and Lower Rate of Overnight Hospitalization in the US Population Over Age 50

Abstract: Objective The aging of the Baby Boomer generation has led to an unprecedented rise in the number of U.S. adults reaching old age, prompting an urgent call for innovative and cost-effective ways to address the increasing health care needs of the aging population. Studying the role of psychosocial factors on health care utilization could offer insight into how to minimize hospitalizations among older adults. Methods We use prospective data from a subsample of 4,735 participants (mean age (SD) = 69 (8.79) years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 44 publications
(57 reference statements)
0
18
1
1
Order By: Relevance
“…Obstacles for healthcare access in older adults have been consistently associated with worsened outcomes and increased all-cause mortality, particularly for those facing social inequalities [27]. Previous research has shown that negative self-perceived aging influences healthcare-seeking behavior, particularly in settings of limited healthcare access [28,29]. Our results suggest that reduced healthcare access, as measured by increases in the social lag index, and lesser number of available hospital beds are associated with increased COVID-19 severity and lethality in older adults, likely reflecting the effect of structural inequalities across Mexican municipalities.…”
Section: Discussionmentioning
confidence: 99%
“…Obstacles for healthcare access in older adults have been consistently associated with worsened outcomes and increased all-cause mortality, particularly for those facing social inequalities [27]. Previous research has shown that negative self-perceived aging influences healthcare-seeking behavior, particularly in settings of limited healthcare access [28,29]. Our results suggest that reduced healthcare access, as measured by increases in the social lag index, and lesser number of available hospital beds are associated with increased COVID-19 severity and lethality in older adults, likely reflecting the effect of structural inequalities across Mexican municipalities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research that did not consider domain-speci c views on aging but looked at overall positive SPA showed that these views can buffer the negative effect of precariousness on health and well-being (23) and promote healthy behavior (24). Positive SPA are also associated with a lower rate of overnight hospitalizations after four years (25). Furthermore, the association of positive SPA and better self-reported physical function in late life is mediated by self-e cacy (8): This means that positive SPA subsequently foster a person's ability to cope successfully with aging-related challenges, which is then later re ected in better self-reported, and, presumably, also objective physical function.…”
Section: Aims and Hypothesesmentioning
confidence: 99%
“…The level of SWB declines later in life (25,26). Regardless of functional limitation, high life satisfaction has been associated with fewer doctor visits and higher use of preventive health care services (27), and fewer overnight hospitalizations (28). Individuals with disabilities spend less time on work and productive activities and more time on passive leisure (29), and they experience increased frustration and decreased activity-related happiness.…”
Section: Frailty and Resiliencementioning
confidence: 99%